Survival analysis of time to opioid use and the role of PTSD-linked stress sensitivity for predicting onset risk for juvenile offenders following adjudication - Wojciechowski, Thomas W. (The prison journal, 2022)
This study sought to understand how PTSD predicts opioid use onset rates and how subsequent exposures to violence also influence this risk following adjudication. Survival analysis was used to examine the moderating role that baseline PTSD status plays for predicting rates of opioid use onset risk following adjudication. Hazard models used to examine the role of time-varying covariates for predicting opioid onset risk following adjudication. PTSD was found to predict significantly greater odds of opioid use initiation. Hazard of introducing opioid use was greater during observation periods in which participants witnessed violence. This effect was greater for PTSD sufferers.